Characterization of the complete mitochondrial genome of a harvesting ant Messor structor (Hymenoptera: Formicidae: Myrmicinae). Issue 6 (3rd June 2022) - Zhang, Xin-Min; Han, Xiu; Liu, Xia; Xu, Zheng-Hui
Abstract: Messor structor (Latreille, 1798) is a keystone ant species in the genus Messor (Formicidae: Myrmicinae). Here, we reported the complete mitochondrial genome of M . structor . The circular mitogenome of M . structor is 17628 bp including 13 protein-coding genes, two ribosomal RNA genes, 22 transfer RNA genes, and a control region. The base composition was AT-biased (84.07%). Phylogenetic analysis suggests that it is closely related to Aphaenogaster famelica . The mitochondrial genome of M . structor will be a good source for understanding molecular evolutionary studies of this species and related ant species.